2017
DOI: 10.1002/jbt.21995
|View full text |Cite
|
Sign up to set email alerts
|

The impact of some natural phenolic compounds on carbonic anhydrase, acetylcholinesterase, butyrylcholinesterase, and α‐glycosidase enzymes: An antidiabetic, anticholinergic, and antiepileptic study

Abstract: Natural products from food and plant sources have been used for medicinal usage for ages. Also, natural products with therapeutic significance are compounds derived from animals, plants, or any microorganism. In this study, chrysin, carvacrol, hesperidin, zingerone, and naringin as natural phenols showed excellent inhibitory effects against human (h) carbonic anhydrase (CA) isoforms I and II (hCA I and II), α-glucosidase (α-Gly), acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). These phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 79 publications
1
96
0
Order By: Relevance
“…hCA II is often associated with several diseases such as glaucoma, osteoporosis, and renal tubular acidosis. [57] AChE is inhibited by surplus substrate molecules, whereas BChE is not. Interestingly, hCA II has been associated with several transporters including the Cl − /HCO 3 − exchanger, the Na + /HCO 3 − cotransporter, and the Na + /H + exchanger.…”
Section: Discussionmentioning
confidence: 98%
“…hCA II is often associated with several diseases such as glaucoma, osteoporosis, and renal tubular acidosis. [57] AChE is inhibited by surplus substrate molecules, whereas BChE is not. Interestingly, hCA II has been associated with several transporters including the Cl − /HCO 3 − exchanger, the Na + /HCO 3 − cotransporter, and the Na + /H + exchanger.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that activating the cholinergic function by inhibiting AChE can be a clinically effective method for treatment of AD. AChE is the key enzymes that play important roles in cholinergic transmission by hydrolyzing the neurotransmitter ACh …”
Section: Resultsmentioning
confidence: 99%
“…α‐Glycosidase inhibitory efficacy of novel N‐substituted tetrahydropyrimidines based on phenylthiourea ( 1a‐d ) was performed using p ‐nitrophenyl‐ d ‐glycopyranoside ( p ‐NPG) as the substrate, conforming to the method of Tao et al Samples were prepared by dissolving 20 mg in 20 mL (EtOH:H 2 O). First, 200 µL of phosphate buffer (PB) was mixed with 40 µL of the enzyme solution in PB (0.15 U/mL, pH 7.4) and 50 to 300 µL of the sample . Multiple solutions in PB were prepared in case of getting full enzyme inhibition.…”
Section: Experimental and Methodsmentioning
confidence: 99%